Play Intervention Applied to Hospitalized Children: Effects on Anxiety and Medical Fear - Benazeera; Priya Reshma Aranha; Yashaswini (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To ease the anxiety and medical fear before intravenous cannulation or blood collection procedures among hospitalized children. METHODOLOGY: This study employed a pre-test, post-test quasi-experimental design during June to August 2023 from the hospital paediatric medicine ward. Sixty school-aged children (aged 6-12) were chosen through purposive sampling. The control group’s data was collected first, followed by a play intervention for the experimental group. Both groups were similar in size. Baseline data on children and parents was gathered using the State-Trait Anxiety Inventory and the Children’s Fear Scale. RESULTS: The children participating in the intervention had a mean age of 9.23±1.65. Notably, a significant portion of both groups experienced respiratory illnesses, with a higher prevalence observed in the control group (33.3%) compared to the intervention group (26.6%). A three-day play intervention significantly improved outcomes for hospitalized children (p<0.001). It helped them manage anxiety both in the general sense (trait anxiety) and specifically related to medical procedures (p<0.001) such as inserting intravenous catheters (IVs) or drawing blood. The study also found a strong correlation between a child’s overall anxiety level and their anxiety around medical procedures (r 0.49, p=0.000). CONCLUSION: Play intervention had a positive impact on state anxiety, trait anxiety and fear about intravenous cannulation or blood collection procedures. Pediatric nurses and parents working together to incorporate play is one of the most important aspects of a child’s hospitalization. This approach focuses on improving health outcomes by making play a part in the healing process.